Perbandingan Perlindungan Hukum bagi Bidan dalam Menjalankan Praktik Keprofesiannya Sebelum dan Sesudah Berlakunya UU Nomor 17 Tahun 2023 tentang Kesehatan - Astuti, Rahayu; Savitri, Aisha Mutiara (HUMANIORUM, 2025)
Legal protection is a protection given to legal subjects in accordance with legal rules, both preventive (prevention) and repressive (countermeasures), both written and unwritten in order to enforce legal regulations. Legal protection is one of the rights of Medical Personnel and Health Personnel based on Law Number 17 of 2023 concerning Health. This research compares legal protection for midwives in carrying out their professional practices before and after the enactment of Law Number 17 of 2023 concerning Health and analyzes the form of legal protection for midwives in handling medical disputes. The research method used is descriptive normative legal research. Meanwhile, the problem approaches used are the statutory approach and the conceptual approach. The research results showed that Law Number 17 of 2023 provides significant changes in the regulations for legal protection, namely they are more integrated and comprehensive and the regulations are clearer regarding the responsibilities and rights of Midwives in health services compared to previous regulations. Another comparison is in Law Number 17 of 2023 concerning Health that the resolution of medical disputes is prioritized through alternative dispute resolution outside of court. However, this law cannot yet be implemented in cases of suspected criminal acts against midwives in 2024, because the Professional Disciplinary Council (MDP) has not yet been formed and there are no recommendations for MDP as an effort to protect the law for Medical Personnel and Health Personnel. Therefore, it is hoped that implementing regulations, technical instructions from Law Number 17 of 2023 concerning Health will soon be prepared, especially regarding aspects of HRM management, guidance and supervision as well as legal protection, especially the mechanism for providing recommendations by the Professional Disciplinary Council (MDP).